Incel dan Konstruksi Gender dalam Interseksi Marginalisasi dan Ekspresi Radikal di X - Pratama, Teguh Agum; Kevin Rasyid Sabili Nasution (Jurnal ILMU KOMUNIKASI, 2025)
This article examines the incel phenomenon as a manifestation of radicalism and misogyny within the construction of gender in the digital era. The urgency of this study lies in the growing influence of incel narratives on X, intensifying gender polarization and the potential for gender-based violence. The research employs a qualitative method with a virtual ethnographic approach and content analysis technique. Post and public comments, as data, were collected through the Keyhole application. The findings indicate the algorithms facilitate the radicalization of masculine identity and amplify radical expressions, underscoring the need for intervention through education and responsible social media regulation.